Preparação e caracterização de hidroxiapatita a partir de resíduos de espinhas do Tambaqui (Colossoma macropomum) para remoção de poluente orgânico. - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2022)
Biomaterials comprise an important group of low-cost materials and exclusive properties, which are currently being applied in several technological areas for the protection and depollution of the environment. The objective of this work was the production, characterization and application of hydroxyapatite from fish waste from Santarém (Western region of Para). The selected samples were the residues of tambaqui spines (Colossoma macropomum), a typical fish of the region and widely consumed by the population, which were discarded by local sellers. Purification efficiency was monitored using X-ray diffraction (XRD), infrared spectroscopy (FTIR), thermal analysis (TG-DSC) and scanning electron microscopy (SEM) techniques. The results revealed that the raw material contained impurities of an organic nature that were removed after physical-chemical purification processes such as calcination, filtration and drying, thus showing that it can be transformed into a value-added product of technological and environmental interest. The adsorption tests with the pollutant showed a degradation efficiency close to 70 % in 3 h, thus showing that hydroxyapatite obtained from tambaqui residues can be used as a cheap source to obtain a cationic organic pollutant adsorbent.
Keywords: Amazônia - Sustentabilidade; Purificação; Adsorção; Poluente; CNPQ::CIÊNCIAS EXATAS E DA TERRA::ÁREA: GEOCIÊNCIAS :: ARQUEOMETRIA; BIODIVERSIDADE, SAÚDE E SUSTENTABILIDADE; BIODIVERSIDADE, SAÚDE E SUSTENTABILIDADE